Dynamic parameter inverse analysis of concrete dams based on Jaya algorithm with Gaussian processes surrogate model. (August 2021) - Kang, Fei; Wu, Yingrui; Li, Junjie; Li, Hongjun
Abstract: A dynamic parameter inverse analysis process for concrete dams based on Gaussian process regression and Jaya algorithm is presented. Gaussian process regression is used to establish a response surface representing the relationship between dynamic elastic modulus and modal parameters (natural frequency and mode shape). The Jaya algorithm is applied for dynamic parameter identification by minimizing the objective function. To verify the performance of the proposed method, we consider a concrete single buttress dam and a hyperbolic concrete arch dam as numerical examples. Numerical results show that Gaussian process regression can significantly improve the parameter identification efficiency without compromising on accuracy. Furthermore, the Jaya algorithm is compared with particle swarm optimization algorithm and genetic algorithm; the results show that the Jaya algorithm is promising in parameter recognition.